Efektivitas Instagram Sebagai Media Promosi Terhadap Minat Pengunjung Wisata Omah Sukuh, Jawa Tengah - Aldefta Adwheputra Anafcsyah, Auflie (Journal of Comprehensive Science, 2024)
Internship is one of the options for students of the Literature-1 program to complete their final project at the Faculty of Business and Economics, Islamic University of Indonesia. The final project of this Internship was completed by the author by studying Omah Sukuh in collaboration with Perum Perhutani. At the time of the internship, the author was placed in agrotourism in charge of inputting data on visitors who came every month, the number of visitors to Omah Suku was still small who came to tour Omah Sukuh. Regarding the problems faced by the tribe's house, the author wants to analyze how effective Instagram social media is to be a place to promote. The internship was carried out for 4 months from February 13, 2023 to May 14, 2023.The author took a qualitative method for the preparation of this internship final project, data collection was carried out by interviews with the company manager of Perum Perhutani and the person in charge of tourism Omah Sukuh. The author has gained a lot of knowledge and skills such as marketing using influencers on Instagram social media is very effective to be used as a place for promotion. The findings from this study can be used to optimize the use of Instagram as a promotional medium, especially in creating content on Instagram reels with interesting content, the use of hashtags and audio that are relevant and trending. Just like what has been done before, but still increased creativity, innovation, and consistency. This can increase visitors who come from viewing content on Instagram uploaded by influencer content.